Simulated dynamic finite-element experiments and automatic assembly synthesis for mechanical design automation. (2018) - Chatziparasidis, Iraklis; Giagopoulos, Dimitrios; Sapidis, Nickolas S.
Engineering-to-order (ETO) companies encounter two major issues greatly affecting them: 1) often, customers request products that exceed a company's previous experience. In this case, these companies are usually proceeding with experiments, using full scale prototypes, to validate a new design; 2) significant time is required for the product to be designed and fully engineered. To present a framework addressing both these issues, we introduce: a) a method that uses finite-element (FE) models and simulated dynamic experiments to deduct new design rules, instead of performing experiments with full scale prototypes; b) a CAD system based on the automatic assembly synthesis model (AASM) that automatically synthesises the final CAD model. The present framework also contains a specific methodology for validating finite element models regarding accuracy for simulated dynamic analysis. Using this framework, a company's design rules can be enriched by simulated experiments, expanding this company's Knowledge Based Engineering (KBE) system.